Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3892/etm.2020.9271
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B exerts hypnotic effects in PCPA‑treated rats by increasing hypothalamic 5‑HT and γ‑aminobutyric acid levels

Abstract: Schisandrin B (SchB) is one of the primary active components of Schisandra chinensis (Turcz.) Baill., a traditional Chinese herb that has been used to treat insomnia for hundreds of years. Our previous studies revealed that SchB exerts sedative and hypnotic effects, increasing the content of γ-aminobutyric acid (GABA) and the expression of its receptors in the brain tissues of rats. 5-hydroxytryptamine (5-HT) is another important neurotransmitter involved in sleep regulation, although, to the best of our knowl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…According to previous reports with minor modification [24,25], the levels of 5-hydroxytryptamine (5-HT), 5-hydroxyindoleacetic acid (5-HIAA), norepinephrine (NE), and dopamine (DA) in the hypothalamus of all rats were evaluated using ELISA under the help of the 5-HT ELISA kit (ER1463, FineTest, Wuhan, China), 5-HIAA ELISA kit (EU2582, FineTest), NE ELISA kit (EU2565, FineTest), and DA ELISA kit (EU0392, FineTest). In brief, 50 μL hypothalamus homogenate samples, standard samples, or blank samples were added into the well, followed by the addition of 50 μL biotin-labeled antibody working solution for 45 min of incubation at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous reports with minor modification [24,25], the levels of 5-hydroxytryptamine (5-HT), 5-hydroxyindoleacetic acid (5-HIAA), norepinephrine (NE), and dopamine (DA) in the hypothalamus of all rats were evaluated using ELISA under the help of the 5-HT ELISA kit (ER1463, FineTest, Wuhan, China), 5-HIAA ELISA kit (EU2582, FineTest), NE ELISA kit (EU2565, FineTest), and DA ELISA kit (EU0392, FineTest). In brief, 50 μL hypothalamus homogenate samples, standard samples, or blank samples were added into the well, followed by the addition of 50 μL biotin-labeled antibody working solution for 45 min of incubation at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, the presence of GABAA receptor subunit α1mRNA in the OB has been described [34] and is the most common GABAAα subunit in adult rodent neurons [35]. In addition, it has been reported that 5-HT depletion could affect GABAA receptor expression in different brain areas [36,37]. We aimed to evaluate aggressive behavior and serotonergic activity in the OB, TPH2, and GABAA α1 mRNA expression in the OB after a single pCPA i.p administration in male rats.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we investigate the potential anticonvulsant properties of schisandrin B using zebrafish larvae and mouse pentyleneterazole (PTZ) seizure tests. Schisandrin B ( Figure 1 ) is one of the main active compounds of Schisandra chinensis —a traditional Chinese herb used for thousands of years to treat some neurobehavioral disorders, including insomnia and dysphoria [ 11 , 12 ]. The experimental studies confirmed the previously known traditional curative properties of Schisandra chinensis extracts [ 12 , 13 ] and demonstrated other biological activities, i.e., anti-inflammatory, antioxidant, and antitumor properties [ 14 ], and possibilities for the medicinal use of this plant and its constituents in the treatment of some neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Schisandrin B ( Figure 1 ) is one of the main active compounds of Schisandra chinensis —a traditional Chinese herb used for thousands of years to treat some neurobehavioral disorders, including insomnia and dysphoria [ 11 , 12 ]. The experimental studies confirmed the previously known traditional curative properties of Schisandra chinensis extracts [ 12 , 13 ] and demonstrated other biological activities, i.e., anti-inflammatory, antioxidant, and antitumor properties [ 14 ], and possibilities for the medicinal use of this plant and its constituents in the treatment of some neurodegenerative diseases. Extracts of Schisandra chinensis fruits improved cognition and learning abilities, prevented some pathological changes in the brain of mice with an intracerebroventricular injection of amyloid-β 1–42 (Aβ 1–42 ) [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%